Universities’ response to new challenges of the time: synthesis of traditions and innovations - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2024)
The challenges facing modern university education are considered. The important mission of higher education in shaping the ideals of the future is emphasised. It is noted that the Belarusian higher education system, being the heiress of Soviet educational practices, is an original national phenomenon formed taking into account the state needs and cultural traditions of the population. Economic and political institutions form an order for the training of specialists, set priorities for state support in the field of economics, and determine the situation on the labour market. The main problem of post-Soviet higher education systems is, first of all, the rejection of their own experience in training specialists. The borrowing of Western samples of educational programmes without proper expertise and adaptation, haste and formalism in the educational process led to the decline of the higher education system, the loss of the authority of the higher school teacher in the eyes of the public. Today, there is a need to develop a kind of roadmap for the future of education as an element of national culture. An improved education model should effectively use modern technological environments, productively respond to the demands of the economy and society, and represent a synthesis of traditions and innovations. The increased attention to the education system is due to the fact that it is in university shifts that the life meanings and values of the younger generation are formed, allowing them to adapt to the challenges of the time.